2012
DOI: 10.5402/2012/943089
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Non-Hodgkin's Lymphoma: An Intercategory Comparison of Microvessel Density

Abstract: Background. This study was aimed at comparing angiogenesis, seen as microvessel density (MVD) in subtypes of non-Hodgkin’s lymphoma (NHL).Methods. In this study, 64 cases of NHL diagnosed over a three-year period were included along with 15 lymph node biopsies of reactive hyperplasia. NHLs were classified using REAL classification, and immunohistochemistry was performed for CD34 in all cases. CD34-stained sections were evaluated for “hot spots,” whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
5
18
0
4
Order By: Relevance
“…2C). As this has been reported for solid tumors and certain non-Hodgkin's lymphomas, including T cell lymphoma (22, 23), we asked if this was associated with increased expression of pro-angiogenic factors such as VEGF. Indeed, VEGF mRNA levels were significantly enhanced in Rpl22 −/− lymphomas (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…2C). As this has been reported for solid tumors and certain non-Hodgkin's lymphomas, including T cell lymphoma (22, 23), we asked if this was associated with increased expression of pro-angiogenic factors such as VEGF. Indeed, VEGF mRNA levels were significantly enhanced in Rpl22 −/− lymphomas (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Positive association between MVD and patient outcome is in contrast with the notion that in hematologic malignancies, as well as in solid tumors the increase of angiogenesis-associated variables is related to adverse prognosis 15,22,28 . Aggarwal et al 20 found higher MVD in aggressive lymphoma such as peripheral T- cell lymphoma and DLBCL, and low MVD in lowgrade lymphomas 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Angiogenesis is a multistep process playing a crucial role in the progression and metastasis of various tumors, including those of visceral organs and hematolymphoid malignancies 20 . Tumor angiogenesis has been well documented both in experimental and clinical studies, and the degree of angiogenesis was closely associated with tumor progression and shorter patient survival in many types of cancer 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Протокол включает два курса R-DHAP: дексаметазон по 40 мг внутривенно в 1-4-й день курса, цитарабин в высоких дозах (НD-Ara-C) 2000 мг/м 2 внутривенно во 2-й день, цисплатин 100 мг/м 2 внутривенно в 1-й день. Применение препаратов платины обеспечивает блокирование ряда механизмов лекарственной устойчивости, поэтому платиносодержащие курсы широко используются в качестве ХТ лимфом второй линии [18,19]. Два курса R-DHAP позволяют оценить химиочувствительность опухоли, которая является важным прогнозирующим фактором, а также дает возможность значительно сократить объем опухолевой массы [20].…”
unclassified